The Impact of Quarantines, Lockdowns, and 'Reopenings' on the Commercialization of Science: Micro and Macro Issues. (17th March 2021) - Siegel, Donald S.; Guerrero, Maribel
Abstract: In 2020, almost all research labs in industry, academia, and the government were shut down for long periods of time by political leaders to control the spread of the coronavirus. We consider the "micro" and "macro" implications of ongoing coronavirus disruptions in scientific research and the dissemination and commercialization of that research. We have identified three key unanswered research questions regarding these unprecedented disruptions: (1) How is the pandemic affecting conventional measures of scientific output (the quantity and quality of basic research) and performance, social networks, and the strategic management of innovation? (2) How is the pandemic affecting technology transfer offices, incubators, accelerators, science and technology parks, and other aspects of the innovation ecosystem? (3) How do pandemic disruptions affect micro‐level factors, such as role conflict, identity, work‐life balance, equity, diversity, inclusion, "championing, " leadership, and organizational justice?